2020
DOI: 10.1523/jneurosci.2235-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Critical Period Plasticity in a Mouse Model of Neurofibromatosis Type 1

Abstract: Neurofibromatosis type 1 (NF1) is a common monogenic neurodevelopmental disorder associated with physical and cognitive problems. The cognitive issues are thought to arise from increased release of the neurotransmitter γ-amino butyric acid (GABA). Modulating the signaling pathways causing increased GABA release in a mouse model of NF1 reverts deficits in hippocampal learning. However, clinical trials based on these approaches have so far been unsuccessful. We therefore used a combination of slice electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…We performed immunohistochemical labeling (see STAR Methods ) for synaptotagmin-2 (Syt2), a specific marker of PV-IN synapses ( Sommeijer and Levelt, 2012 ; Bouhours et al, 2017 ; van Lier et al, 2020 ), and confirmed that Syt2-positive boutons were perisomatic and PV positive ( Figure S8A ). We then quantified the number of PV-IN boutons surrounding the cell bodies of PCs in all experimental groups ( Figure S8B ) and found a small but statistically significant decrease in the number of Syt2-positive puncta around PCs in Scn1a +/− P16–P21 SUDEP relative to Scn1a +/− P16–P21 SURVIVOR and WT P16–P21 and in Scn1a +/− P35–P56 relative to WT P35–P56 ( Figure S8C ).…”
Section: Resultsmentioning
confidence: 74%
“…We performed immunohistochemical labeling (see STAR Methods ) for synaptotagmin-2 (Syt2), a specific marker of PV-IN synapses ( Sommeijer and Levelt, 2012 ; Bouhours et al, 2017 ; van Lier et al, 2020 ), and confirmed that Syt2-positive boutons were perisomatic and PV positive ( Figure S8A ). We then quantified the number of PV-IN boutons surrounding the cell bodies of PCs in all experimental groups ( Figure S8B ) and found a small but statistically significant decrease in the number of Syt2-positive puncta around PCs in Scn1a +/− P16–P21 SUDEP relative to Scn1a +/− P16–P21 SURVIVOR and WT P16–P21 and in Scn1a +/− P35–P56 relative to WT P35–P56 ( Figure S8C ).…”
Section: Resultsmentioning
confidence: 74%
“…Furthermore, myelin‐based treatments in adults are envisioned. The current view that neurological issues in developmental/genetic diseases are unavoidable and permanent is supported by developmental processes occurring within an established window of time in NF1 (van Lier et al, 2020; Wang, Kim, et al, 2012), which can limit therapeutic windows. Nonetheless, experimental evidence from several groups contrast this view and envision successful treatments in postnatal‐adult patients (Barco et al, 2006; Costa et al, 2002; Cui et al, 2008; Ho et al, 2007; Lee et al, 2014; Li et al, 2005; López‐Juárez et al, 2017; Pagani et al, 2009; Thomas & Huganir, 2004; Viosca et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity defects may be seen in conditions marked by impaired neurodevelopment. In a mouse model of neurofibromatosis type 1, a model to study ASD, high levels of inhibition were observed in the adult V1, with no overt effects on early cortical development [73]. The authors found increased inhibition during development to be the cause of early closure of the CP for OD plasticity.…”
Section: Ocular-dominance Plasticitymentioning
confidence: 97%